Pengembangan Kemampuan Life Skills Siswa dengan Penerapan Model Problem Based Learning - Arina Mufrihah; Rusmiyati Rusmiyati; Adirasa Hadi Prasetyo; Mafruhah Mafruhah (STKIP PGRI SUMENEP, 2020)
This research aims to improve one of the student's life skills using Problem Based Learning (PBL) model. It applied a classroom action research design (PTK) which was carried out for three cycles. The PBL model used in this study is integrated into Civics subjects by looking at the accompanying impact, not the instructional impact of Civics learning. This study implemented observation as the instrument of research. Through not only the result of the observation sheet from the student direct life skills aspects which the action research was carried out but also observe the teacher activity using the PBL model and the student responses in using those aforementioned model. The technique used to analyze the data is divided into two techniques that are both qualitative and quantitative data analysis. The results showed that the application of the PBL model could not develop the students' life skills aspects.